2013
DOI: 10.1603/me11219
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Anopheline Mosquitoes (Diptera: Culicidae) in the Central Atlantic Forest Biodiversity Corridor, Southeastern Brazil

Abstract: Knowledge of the fauna composition of anopheline mosquitoes, their ecological aspects and behavior, and influence of climatic variables on their population dynamics can help in understanding the transmission of Plasmodium parasites and thus develop more efficient strategies for the control of malaria. In the Central Atlantic Forest Biodiversity Corridor, southeastern Brazil, foci of introduced malaria have been reported among people returning from the Amazon region, north Brazil. Our objective was to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The numerous water reservoirs from recently constructed hydroelectric plants increased the number of suitable larval habitats for An. darlingi as well as for other potential Nyssorhynchus malaria vectors, such as species of the Albitarsis and Triannulatus complexes (Gomes et al 2008, 2013, Limongi et al 2008, Meneguzzi et al 2009, Da Silva et al 2013, McKeon et al 2013, Ribeiro et al 2013). Along the coastal lowlands, introduced malaria cases and/or small epidemics have emerged on occasion and localities with brackish water and Nyssorhynchus and An.…”
Section: Malaria In the Extra-amazonian (Non-endemic) Regionmentioning
confidence: 99%
“…The numerous water reservoirs from recently constructed hydroelectric plants increased the number of suitable larval habitats for An. darlingi as well as for other potential Nyssorhynchus malaria vectors, such as species of the Albitarsis and Triannulatus complexes (Gomes et al 2008, 2013, Limongi et al 2008, Meneguzzi et al 2009, Da Silva et al 2013, McKeon et al 2013, Ribeiro et al 2013). Along the coastal lowlands, introduced malaria cases and/or small epidemics have emerged on occasion and localities with brackish water and Nyssorhynchus and An.…”
Section: Malaria In the Extra-amazonian (Non-endemic) Regionmentioning
confidence: 99%
“…The presence of vectors is a determining factor for transmission and for assessing receptivity conditions (Azevedo 1997, Rezende et al 2009, 2013, Laporta et al 2011, da Silva et al 2013, Duarte et al 2013, Neves et al 2013). A study conducted in 2009 by the Brazilian Health System showed that several species occur in RJ.…”
Section: Discussionmentioning
confidence: 99%
“…evansae and Anopheles (Nyssorhynchus) oswaldoi (Peryassú, 1922), even in low frequency, presents epidemiological importance, due to the potential transmission of malaria by these species (Consoli & Lourenço-de-Oliveira 1994, Forattini 2002. Silva et al (2013), in a study conducted in Sooretama Biological Reserve, in the State of Espírito Santo, incriminated An. (Nys.)…”
Section: Discussionmentioning
confidence: 99%
“…The association between mosquitoes and these diseases has stimulated researches on the fauna, geographic distribution and ecology of these insects, especially in areas with potential risk of pathogen transmission. In the State of Espírito Santo, the few existing studies on the fauna characterization and diversity of mosquitoes are directed to Anophelinae subfamily and areas of potential risk of malaria (Andrade & Brandão 1957, Deane et al 1968, Natal et al 2007, Meneguzzi et al 2009, Rezende et al 2009a, b, 2013, Silva et al 2013). In the mountainous region of Espírito Santo, where sporadic cases of malaria are notified, studies have incriminated Anopheles (Kerteszia) cruzii Dyar & Knab, 1908 as the main vector of Plasmodium vivax (Grassi & Feletti, 1890) (Rezende et al 2009b(Rezende et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation